Development of the System of Continuous Entrepreneurial Education: Problems and Solutions - Sergey Yu. Naumov; Larisa V. Konstantinova (Высшее образование в России)
The article addresses the issues concerning the formation of the continuous entrepreneurial education system taking into account the need to develop human resources of small and mediumsized businesses. The authors reveal the main problems that serve as the barriers to the formation and standardization of such a system in our society. The article defines its main goals and levels, highlights the experience and promising forms of teaching entrepreneurship to schoolchildren with the participation of universities. The basic models of entrepreneurial education in higher education are presented and characterized. The authors dwell on the ways of increasing the efficiency of business education of adults and forms of teaching entrepreneurship to older people, formulate the proposals, which will facilitate institutionalization of the integrated system of continuous entrepreneurial education.